Lewis Acid Mediated Selective Monohydrolysis of Geminal Diesters: Synthesis of Functionalized Malonic Acid Half Esters - Ilangovan, Andivelu; Kumar, Rajendran Ganesh; Kaushik, Mahabir Prasad (Synlett, 2012)
Geminal diesters, N-alkyl/aryl-2,2-bis(ethoxycarbonyl)vinylamines, were found to undergo selective hydrolysis in the presence of BF3·OEt2 at room temperature to give the corresponding half esters. Neighboring group participation by nitrogen in the hydrolysis was observed. This method is useful for the preparation of highly functionalized malonic acid half esters.
Keywords: Lewis acid; boron trifluoride; geminal diesters; hydrolysis; esters